O PROCESSO DE CONSTRUÇÃO DA MORAL E DA COGNIÇÃO DE CRIANÇAS COM DEFICIÊNCIA INTELECTUAL: INDÍCIOS DE INTERFERÊNCIAS ESCOLARES - Schipper, Carla Maria de (2015)
This study aims to demonstrate the way in which people with Intellectual Disability conceive and develop their ability to perceive moral values related to the construction of the notion of justice and understand the singularities of his reasoning through the contributions of Genetic Epistemology. We conducted an exploratory and empirical study using Piaget`s Clinical Method, with twenty-seven intellectually disabled children and preadolescents to show possible signs of school interferences in the formation of morality. We evaluated through twelve operational tests the development of the students` reasoning. Following this, seventeen moral dilemmas were presented with the aim of observing the development of the notion of justice. Finally, seven teachers and four members of the pedagogical team were interviewed in order to assess moral education procedures. On the cognitive level we noted the absence of reversibility, decentration and non-conservation, resulting in consequences for cognitive and moral development. On the level of social and affective interaction, unquestioning obedience to adults as a result of unilateral respect arising from the historically built belief in their inability to be autonomous which in turn produced the submission of people with Intellectual Disabilities and, as a consequence, unilateral respect for adults. With regard to school interferences, we found negative signs of influences such as unilateral respect, conflict solution methods and the use of prizes and punishment. On the other hand, we also noted positive signs, such as cooperation, mutual respect and the methods used in everyday school life. In relation cognition / moral, we conclude that the development of moral, walks to an uneven speed. In moral cooperation and solidarity are valued and encouraged, however, cognitively constructivist strategies are not employed, contrariwise they work with students as if they remained in the preoperative level and use methodology and behavioral strategies.